Fetishism and visual culture in Later Neolithic Southeast Italy. (1st October 2016) - Skeates, Robin
ABSTRACT: The term 'fetish' has been used since the sixteenth century to refer to indigenous 'power objects', perceived to embody positive supernatural energy. This concept is explored here with reference to the visual culture of the Later Neolithic in Southeast Italy (5800–4100bc ). During this period, many aspects of the material world were ascribed a greater visual significance, being modelled into more varied art-forms and highlighted by more innovative and elaborate decoration, ritual performances and special deposits. A culturally specific range of powerful bodily and abstract symbols unified and animated these material forms, to the extent that we can talk of a fetishistic way of seeing and visual culture. These may have been used strategically to highlight and strengthen social connections, distinctions and boundaries. Ultimately, these social dynamics related to tensions surrounding the final transition to a fully agricultural way of life in Neolithic Southeast Italy.